Frontal deficits differentiate progressive supranuclear palsy from Parkinson's disease. Issue 1 (16th September 2014) - Lee, Young‐Eun C.; Williams, David R.; Anderson, Jacqueline F. I.
Abstract : The clinical differentiation of progressive supranuclear palsy from Parkinson's disease can be challenging, due to overlapping clinical features and a lack of diagnostic markers. Abnormalities in cognitive function form part of the clinical spectrums of these diseases and distinctive cognitive profiles may be helpful in differentiating these diseases in the diagnostic period. A comprehensive neuropsychological test battery was administered to 12 patients with clinically diagnosed progressive supranuclear palsy and 12 patients with Parkinson's disease matched for age and disease duration. Effect size (Cohen's d ) was calculated for cognitive tests that were significantly different between groups. Patients with progressive supranuclear palsy performed significantly worse than those with Parkinson's disease on measures of processing speed, verbal fluency, planning, verbal abstract reasoning, verbal memory, and made more perseverative responses on a set shifting task. Measures of executive function, manual dexterity and processing speed were most diagnostically useful (Cohen's d > 2.0) in differentiating between progressive supranuclear palsy and Parkinson's disease. These findings suggest that more severe and prominent 'frontal' cognitive deficits in patients with progressive parkinsonism would be helpful in predicting progressive supranuclear palsy rather than Parkinson's disease and these findings may contribute to the development of diagnostic criteria.